1991
DOI: 10.1007/bf00319709
|View full text |Cite
|
Sign up to set email alerts
|

Transient loss of consciousness: The value of the history for distinguishing seizure from syncope

Abstract: We studied 94 consecutive patients (age 15 or over) to investigate which aspects of the history and clinical findings help to distinguish seizures from syncope and related conditions. Clonic movements or automatism observed by an eyewitness classified an event as a seizure. The seizure group consisted of 41 patients and the syncope group of 53 patients. The likelihood ratio was used to calculate the predictive power of single findings and logistic regression to analyse combinations of findings. The best discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
1
10

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 19 publications
1
113
1
10
Order By: Relevance
“…Urinary incontinence was present in 19.1% of our patients with reflex syncope, confirming earlier findings that urinary incontinence provides no additional evidence for or against the diagnosis of a seizure [15]. The duration of the TLOC was <5 minutes in 73.7% of the subjects in our study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Urinary incontinence was present in 19.1% of our patients with reflex syncope, confirming earlier findings that urinary incontinence provides no additional evidence for or against the diagnosis of a seizure [15]. The duration of the TLOC was <5 minutes in 73.7% of the subjects in our study.…”
Section: Discussionsupporting
confidence: 87%
“…The duration of the TLOC was <5 minutes in 73.7% of the subjects in our study. Although Hoefnagels et al [15] suggested that a duration of loss of consciousness of >5 minutes and postictal confusion are suggestive of epilepsy, 13.5% of our patients with reflex syncope suffered from prolonged loss of consciousness and postictal confusion was observed in 10% of our patients with reflex syncope. Prolonged periods of unconsciousness or postictal confusion ( ‡5 minutes) in syncope patients may be explained by continuing hypotension, for instance, when remaining in an upright position during or after the episode.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In particular, differential diagnosis between seizures and syncope attacks may be difficult (7,9). Nonetheless, history, physical examination and electrocardiography have a combined diagnostic yield of 50% in the assessment of syncope (10).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of consciousness was classified as seizure (seizure group) or syncope attack and related disorder (syncope group) on the basis of history and clinical examination following previously published principles (7). A seizure had to include repetitive tonic and/or clonic movements or automatisms and the diagnosis was supported by blue face, frothing at the mouth and disorientation or sleepiness after the event.…”
Section: Methodsmentioning
confidence: 99%